The colour-magnitude relation of simulated early-type galaxies as a function of their kinematics - Zenocratti, Lucas Jesús (2021)
Early-type (ET) galaxies (both elliptical and lenticular) define the well-known red sequence or colour-magnitude relation (CMR) in the colour-magnitude diagram (CMD). In this work, we present results of the study of that relation at different redshifts z in cosmological numerical simulations. In particular, we explore its evolution from z = 2 to z = 0, selecting a sample of simulated objects that display similar properties of observed ET galaxies in the Local Universe. The average rotation speed of those objects is used to determine if their stellar kinematics correlates with their position in the diagram, as well as with other properties. Evolution of fast- and slow-rotators over the CMD at different redshifts and changes in their kinematical behaviour is also analysed. Results shown here are part of a project aimed at identifying the processes that originated the CMR at z = 0, performing a comprehensive comparison between simulated and observed ET galaxies.